RADICALISM IN ISLAMIC HISTORY - Rokhmah Ulfah (Pascasarjana Universitas Wahid hasyim Semarang, 2013)
Islam is love and peace religion that brings justice, equality and moderation. The word Islam comes from salima means surrender, submission and peace. So that being a Muslim means spread and build a peace in the world. In fact nowadays, Islam has appeared as a violent religion bringing hatred. Indeed, this has blotted Islamic message namely peacefulness. Radical movement has a deep historical root in Islam called khawarij. Khawarij emerged when the arbitration (tahkim) conducted between Ali bin Abi Thalib and Muawiyah in Shiffin war and it was a fundamentalist religion movement. The coming out of Wahabi with their militan followers shows neo-khawarij, radical movement in Islam.Keywords: violence, extremism, conflict, radicalism